A Study of Psychiatric Comorbidity (Anxiety and Depression) in Patients of Head and Neck Cancer Undergoing Radiotherapy - Puneet Kamal, Abhishek Arora, Manjit Singh, Parshotam Dass Garg, Rajiv Arora, Sukrantvir, Nittu Sidhu (International Journal of Innovative Research in Medical Science, 2018)
Objective: To assess the symptoms of depression and anxiety in patients with head and neck cancer undergoing radiotherapy. Material and Methods: The present study was conducted in Psychiatry department, Government Medical College, Amritsar. A sample size of 34 patients was taken who were diagnosed with Head and Neck Cancer and were undergoing radiotherapy at Department of Radiotherapy, Government Medical College, Amritsar. Hospital Anxiety and Depression Scale (HADS) was used for the assessment of symptoms of anxiety and depression. Results: Out of 34 participants in the study 3 were having anxiety symptoms and 16 were having depression symptoms. Females were having more anxiety as compared to males. During the course of radiotherapy the symptoms of depression increased. Conclusion: The findings suggest that rate of depression increased as the duration of cancer increases. 47% of patients have depression and 8.8% of patients have anxiety.